Respuesta :
12x + 10 + 4y is equivalent to
2(6x + 5 + 2y).
This is because
2(6x + 5 + 2y) =
2 * 6x + 2 * 5 + 2 * 2y =
12x + 10 + 4y
2(6x + 5 + 2y).
This is because
2(6x + 5 + 2y) =
2 * 6x + 2 * 5 + 2 * 2y =
12x + 10 + 4y
12x + 10 + 4y= 2(6x + 5 + 2y)
Multiply it out
=2(6x + 5 + 2y)
distribute 2 to every term in parentheses
=(2*6x) + (2*5) + (2*2y)
=12x + 10 + 4y
ANSWER: Last choice 2(6x + 5 + 2y)
Hope this helps! :)
Multiply it out
=2(6x + 5 + 2y)
distribute 2 to every term in parentheses
=(2*6x) + (2*5) + (2*2y)
=12x + 10 + 4y
ANSWER: Last choice 2(6x + 5 + 2y)
Hope this helps! :)